Dmp53 activates the hippo pathway to promote cell death in response to DNA damage. - Colombani, J.; Polesello, C.; Josue, F.; Tapon, N. (Current Biology, 2006)
Developmental and environmental signals control a precise program of growth, proliferation, and cell death. This program ensures that animals reach, but do not exceed, their typical size . Understanding how cells sense the limits of tissue size and respond accordingly by exiting the cell cycle or undergoing apoptosis has important implications for both developmental and cancer biology. The Hippo (Hpo) pathway comprises the kinases Hpo and Warts/Lats (Wts), the adaptors Salvador (Sav) and Mob1 as a tumor suppressor (Mats), the cytoskeletal proteins Expanded and Merlin, and the transcriptional cofactor Yorkie (Yki) . This pathway has been shown to restrict cell division and promote apoptosis. The caspase repressor DIAP1 appears to be a primary target of the Hpo pathway in cell-death control. Firstly, Hpo promotes DIAP1 phosphorylation, likely decreasing its stability. Secondly, Wts phosphorylates and inactivates Yki, decreasing DIAP1 transcription. Although we understand some of the events downstream of the Hpo kinase, its mode of activation remains mysterious. Here, we show that Hpo can be activated by Ionizing Radiations (IR) in a Dmp53 (Drosophila melanogaster p53)-dependent manner and that Hpo is required (though not absolutely) for the cell death response elicited by IR or Dmp53 ectopic expression.